Rational Design and Synthesis of 3-Morpholine Linked Aromatic-Imino-1H-Indoles as Novel Kv1.5 Channel Inhibitors Sharing Vasodilation Effects - Qin, Wei; Li, Yi-Heng; Tong, Jing; Wu, Jie; Zhao, Dong; Li, Hui-Jin; Xing, Lu; He, Chun-Xia; Zhou, Xin; Li, Peng-Quan; Meng, Ge; Wu, Shao-Ping; et al. (Frontiers in Molecular Biosciences, 2022)
Atrial fibrillation (AF) as the most common clinical sustained arrhythmia, clinical therapeutic drugs have the low atrial selectivity and might cause more severe ventricle arrhythmias while stopping AF. As an anti-AF drug target with highly selectivity on the atrial muscle cells, undetermined crystal structure of Kv1.5 potassium channel impeded further new drug development. Herein, the simulated 3D structure of Kv1.5 as the drug target, a series of 3-morpholine linked aromatic amino substituted 1H-indoles as novel Kv1.5 channel inhibitors were designed and synthesized based on target-ligand interaction analysis. The synthesis route was practical starting from commercially available material and the chemical structures of target compounds were characterized. It was indicated that compounds T16 and T5 (100 μM) exhibited favorable inhibitory activity against Kv1.5 channel with inhibition rate of 70.8% and 57.5% by a patch clamp technique. All compounds did not exhibit off-target effects against other drug targets, which denoted some selectivity on Kv1.5 channel. Interestingly, twelve compounds exhibited favorable vasodilation activity on pre-contracted arterial rings in vitro using KCl or phenylephrine (PE) by a Myograph. The vasodilation rates of compounds T16 and T4 (100 μM) even reached over 90%, which would provide potential lead compounds for both anti-AF and anti-hypertension new drug development.